Makna Kehadiran Dokter dalam Perspektif Hukum Kesehatan: Analisis On-Site, On-Call, dan Home-Call dalam Pelayanan Gawat Darurat (Pusat Riset dan Inovasi Nasional, 2026)
Emergency medical care constitutes a fundamental patient right and an institutional obligation of hospitals that must be provided without temporal discrimination. However, in practice and public discourse, the meaning of “physician presence” is often narrowly reduced to physical presence alone, giving rise to allegations of medical negligence, particularly during weekends or outside regular working hours. This distorted understanding risks generating legal injustice, undermining the dignity of the medical profession, and encouraging defensive medical practice. This article aims to analyze the meaning of physician presence from a health law perspective through theoretical, normative, and systemic approaches, by distinguishing models of physician presence as on-site, on-call, and home-call/teleconsultation in emergency care services. This study employs a normative legal research method using statutory, conceptual, and limited comparative approaches. The analysis examines Law Number 17 of 2023 on Health, Government Regulation Number 28 of 2024, as well as health law literature and emergency care practices. The analysis demonstrates that, in legal terms, physician presence is not synonymous with physical presence, but rather should be understood as process-based professional responsibility, provided that care is delivered in accordance with professional standards, service standards, and an adequate triage system. Physician presence must be reconstructed as the presence of professional responsibility within an integrated emergency care system. Legal assessment in health law should be grounded in process and system integrity, rather than solely on clinical outcomes or public perception.